2020
DOI: 10.2147/prbm.s268643
|View full text |Cite
|
Sign up to set email alerts
|

<p>Big Five Personality Traits and Gratitude: The Role of Emotional Intelligence</p>

Abstract: Background Among many possible variables that can be associated with gratitude, researchers list personality traits. Considering that these relationships are not always consistent, the first purpose of the present study was to verify how the Big Five factors connect to dispositional gratitude in a sample of Polish participants. The second purpose was to assess the unique contribution of personality traits on gratitude with multiple regression analyses. Moreover, because much remains to be learned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 93 publications
(151 reference statements)
1
10
0
1
Order By: Relevance
“…Quantitative and qualitative studies of the antecedents and consequences of gratitude (Reckart et al 2017) have shown that gratitude tends to be associated with personality traits (McCullough et al 2001;Szcześniak et al 2020a), various dimensions of psychological wellbeing (Wood et al 2009;Lin 2015aLin , 2015bVoci et al 2019), physical health (Kaczmarek et al 2015;Krause et al 2015;Lavelock et al 2016;O'Connell and Killeen-Byrt 2018;Gallagher et al 2020), quality of social relationships (Algoe et al 2008;Layous and Lyubomirsky 2014), and religiosity (Lambert et al 2009). With respect to the latter correlate, there is some evidence that highly religious people are inclined to be more grateful than their less religious counterparts (Kraus et al 2015).…”
Section: Religiosity and Dispositional Gratitudementioning
confidence: 99%
“…Quantitative and qualitative studies of the antecedents and consequences of gratitude (Reckart et al 2017) have shown that gratitude tends to be associated with personality traits (McCullough et al 2001;Szcześniak et al 2020a), various dimensions of psychological wellbeing (Wood et al 2009;Lin 2015aLin , 2015bVoci et al 2019), physical health (Kaczmarek et al 2015;Krause et al 2015;Lavelock et al 2016;O'Connell and Killeen-Byrt 2018;Gallagher et al 2020), quality of social relationships (Algoe et al 2008;Layous and Lyubomirsky 2014), and religiosity (Lambert et al 2009). With respect to the latter correlate, there is some evidence that highly religious people are inclined to be more grateful than their less religious counterparts (Kraus et al 2015).…”
Section: Religiosity and Dispositional Gratitudementioning
confidence: 99%
“…Keeping in view, the top management can assign responsibilities to the male and female managers based on their EI strengths to boost organizational performance. 91 …”
Section: Discussionmentioning
confidence: 99%
“…Wyniki potwierdziły istotną rolę zdolności emocjonalnych jako mediatora w szczególności pomiędzy stabilnością emocjonalną, ugodowością i ekstrawersją a optymizmem oraz pomiędzy ekstrawersją, stabilnością emocjonalną i sumiennością a nadzieją (Di Fabio i in., 2018). Inteligencja emocjonalna okazała się być również zmienną pośredniczącą między czterema wymiarami osobowości (ekstrawersja, otwartość na doświadczenie, życzliwość i sumienność) a wdzięcznością (Szcześniak, Rodzeń, Malinowska, Kroplewski, 2020).…”
Section: Temperamentalne Uwarunkowania Inteligencji Emocjonalnej 61 Inteligencja Emocjonalna a Różne Cechy Osobowościunclassified